Analytic expressions for the kinetic decoupling of WIMPs. Issue 4 (May 2016) - Visinelli, Luca
Abstract: We present a general expression for the values of the average kinetic energy and of the temperature of kinetic decoupling of a WIMP, valid for any cosmological model. We show an example of the usage of our solution when the Hubble rate has a power-law dependence on temperature, and we show results for the specific cases of kination cosmology and low-temperature reheating cosmology.